Pengembangan dan validasi media lagu interaktif untuk pembelajaran IPA materi organ pencernaan di sekolah dasar - Nisa, Khairun; Desstya, Anatri (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study aims to develop interactive song media as an innovative solution in learning digestive organ material and the effectiveness of the media on learning outcomes of elementary school students. The background of the research is the low student understanding of digestive organ material due to conventional learning approaches that are less interesting. The research used the Research and Development (R&D) method by developing a product in the form of a song learning tool based on the human digestive system. which was carried out at SD Negeri 3 Wadung Getas. The research phase was carried out through 6 stages, namely potential and problems, information gathering, product design, design assessment, design review and product trial. The media was designed by integrating songs, animations, visualizations about digestive organs, and interactive features that allow students to explore the material independently. The research subjects consisted of 28 fifth grade students, 1 media expert, and 1 material expert. The results showed that a) an educational multimedia music video product for grade 5 elementary school students with content about the digestive system has been produced. This material can be found in Topic 3, Subtopic 1, Lesson 2 about Processed Foods in the Digestive System in the form of a video packed with a duration of 2 minutes 55 seconds, b) supported by communication experts with a percentage score of 97% and material experts with a percentage score of 90% in the good category. Effectiveness tests using pretests and posttests showed a significant increase in student understanding, with an average score increasing from 58.57 to 87.14 and an N-gain value of 0.69 (Medium category). This research proves that interactive song media is effective in improving students' understanding of digestive organ material. The media successfully accommodates various learning styles through a multimodal approach that combines audio, visual, and interactive elements. The implication of the research shows the potential of using interactive digital media in improving the quality of science learning in elementary schools.